Language, Ideology, and Power in Kamala Harris’s Speech: Critical Discourse Analysis - Wibhisana, Made Dwika; Ayomi, Putu Nur; Maharani, Ni Putu Devi (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
Political speech is a strategy to persuade the political goals and interests to the audience. This study investigates the process of Critical Discourse Analysis in Kamala Harris's speech by using Three-Dimensional Model proposed by Fairclough. The data analysis was conducted by a descriptive qualitative method. This study showed that Kamala Harris represented the Democrat Party's principles, equal opportunity, and voting rights through the speech. Discursive analysis showed that Kamala Harris addressed this speech to some particular societal stakeholders, such as the feminist movement, minority groups, so on. On the other hand, social analysis represented the social effects, such as the first Indigenous cabinet secretary has confirmed. The most dominant ideology in this speech is membership/self-identity. In textual analysis, Kamala Harris also showed the one who has equality, liberty, and justice on her ideological values.